DOP37 Large differences in IBD care and education across Europe, first results of the pan-European VIPER survey. (27th May 2021) - Král, J; Nakov, R; Lanska, V; Barberio, B; Benech, N; Blesl, A; Brunet, E; Capela, T L; Derikx, L A A P; Dragoni, G; Eek, A; Frias-Gomes, C; et al.
Abstract: Background: More than 2.5 million people in Europe suffer from inflammatory bowel diseases (IBD). IBD affects the quality of life, but also has important consequences for health systems. As IBD care and education might differ and might be linked to Gross Domestic Product (GDP), we conducted this European Variation In ibd PracticE suRvey (VIPER) to study potential differences. Methods: This trainee-initiated survey, run through SurveyMonkey®, consisted of 47 questions inquiring basic demographics, IBD training and clinical care. The survey was distributed through social media and national GI societies from December 2020 - January 2021. Results were compared according to GDP per capita, for which countries were divided into 2 groups (low/high income, according to the World Bank). Differences between groups were calculated using the chi2 statistic. Results: The online survey was completed by 1268 participants from 39 European countries (Figure 1). Most of the participants are specialists (65.3 %), followed by fellows in training (>/< 3 years, 19.1%, 15.6 %). Majority of the responders are working in academic institutions (50.4 %), others in public/district hospitals (33.3 %) or private practices (16.3 %). Despite significant differences in access to IBD-specific training between high (56.4%) and low (38.5%) GDP countries (p<0.001), majority of clinicians feels comfortable in treating IBD (77.2% vs 72.0%, p=0.04). Interestingly, a difference in availability of dedicated IBD units could be observed (58.5% vs 39.7%, p<0.001), as well as an inequality in multidisciplinary meetings (72.6% vs 40.2%, p<0.001), which often take place on a weekly basis (53.0%) (Figure 2 ). In high GDP countries, IBD nurses are more common (86.2%) than in low GDP countries (36.0%, p<0.001), which is mirrored by differences in nurse-led IBD clinics (40.6% vs 13.8%, p<0.001). IBD dieticians (32.4% vs 16.6%) and psychologists (16.7% vs 7.5%) are mainly present in high GDP countries (p<0.001). In the current COVID era, telemedicine is available in 58.4% vs 21.4% of the high/low GDP countries respectively (p<0.001), as well as urgent flare clinics (58.6% vs 38.7%, p<0.001) and endoscopy within 24 hours if needed (83.0% vs 86.7% p=0.1). Treat-to-target approaches are implemented everywhere (85.0%), though access to biologicals and small molecules differs significantly (Figure 3 ). Almost all (94.7%) use faecal calprotectin for routine monitoring, whereas half also use intestinal ultrasound (47.9%). Conclusion: A lot of variability in IBD practice exists across Europe, with marked differences between high vs low GDP countries. Further work is required to help address some of these inequalities, aiming to improve and standardise IBD care across Europe.